Taxonomic status of Andersen’s fruit-eating bat (Artibeus jamaicensis aequatorialis) and revised classification of Artibeus (Chiroptera: Phyllostomidae) - Larsen, Peter A.; Marchán-Rivadeneira, María R.; Baker, Robert J. (Zootaxa, 2010)
Fruit-eating bats of the genus Artibeus are widely distributed across the Neotropics and are one of the most recently evolved assemblages of the family Phyllostomidae. Although the taxonomy and systematics of species of Artibeus has been the subject of an intense historical debate, the most current taxonomic arrangements recognize approximately eleven species within the genus. However, recent phylogenetic studies indicate that species diversity within South and Middle American populations of Artibeus is underestimated. South American populations referable to A. jamaicensis aequatorialis are of considerable interest because previous studies of mitochondrial DNA variation identified potential species level variation west of the Andes Mountains. In this study we use morphometric and genetic data (nuclear AFLPs) to investigate the taxonomic status of A. j. aequatorialis. Our results indicate that elevating aequatorialis to species level is appropriate based on statistically supported reciprocal monophyly in mitochondrial and nuclear datasets and diagnostic morphological characters. In light of our results, and of those presented elsewhere, we provide a revised classification of the genus.